Anti-citrullinated Protein Antibody Generation, Pathogenesis, Clinical Application, and Prospects - Liu, Jiaxi; Gao, Jinfang; Wu, Zewen; Mi, Liangyu; Li, Na; Wang, Yajing; Peng, Xinyue; Xu, Ke; Wu, Fengping; Zhang, Liyun (Frontiers in Medicine, 2022)
Anti-citrullinated protein antibodies (ACPAs) are autoantibodies commonly observed in patients with rheumatoid arthritis (RA). Currently, most of the mechanisms of ACPA formation and bone destruction are well understood, however, some unknown mechanisms still exist. There have been many new advances in ACPA-related clinical applications and targeted therapies. However, the existence of different ACPA subtypes is a limitation of targeted therapy. Herein, we present an overview of the process of ACPA generation, the underlying pathogenesis, and relevant clinical application and prospects.